Next Generation Sequencing (NGS) Everywhere: “Seq it out” the New Paradigm for Labs - Khan, Sikandar Hayat (Pakistan Armed Forces Medical Journal, 2026)
The diagnostic industry in recent times had demonstrated an exponential growth, aiming for more innovative and pioneering efforts to broaden the horizon of precision diagnostics. Witnessing a biotechnological cloudburst boom allowing us to leapfrog from prosaic diagnostics to unfolding the molecular mysteries in genome. The nascency of novel analytical methodologies have empowered to learn the human genetic code sequence. This amplification of DNA served as an “ice breaker” moment for the diagnostic industry to push further the scientific momentum to allow technology to translate preliminary “Sanger sequencing” to accomplish the “Human Genome Project” (HGP).1 The generational growth enhanced sequencing yield by next generational sequencing (NGS), allowing higher coverage, read length and depth, potentiated further by precise & accurate bioinformatics allowing manageable translation to clinics at desirable scale. Wholesome management systems like Maser (Management and Analysis System for Enormous Reads) has allowed to dig deep to terabytes with more clinical flexibility.2